Defining the sequence requirements for recruitment to the Nab3 nuclear granule - Snyder, Samuel Jackson, author; Ross, Eric D., advisor; Di Pietro, Santiago, committee member; Woerman, Amanda, committee member (Colorado State University. Libraries, 2025)
Compartmentalization of cellular components into liquid-liquid phase separated (LLPS) condensates is a process dependent upon intrinsically disordered protein regions (IDRs). Multiple different types of condensates coexist within a cell yet are able to maintain specificity of IDR partitioning. Different models of IDR function have been developed to describe selective recruitment, yet the fundamental properties of IDRs allowing for specificity remain poorly understood. The amino acids within a peptide govern overall biophysical properties, and thus amino acid composition may describe IDR condensate specificity; for this purpose, yeast stress granules (SGs) and the Nab3 nuclear granule were interrogated and computationally quantified. Domains of similar composition to a SG-localizing synthetic domain readily assembled into SGs, but domains of similar composition to the Nab3 prion-like domain (PrLD) had widely variable degrees of assembly incompletely described by composition alone. To further characterize the sequence requirements of the Nab3 granule, the Nab3 PrLD was functionally replaced with a library of PrLDs and synthetic domains and tested for granule assembly. Reduced dispersion of Q residues correlated with increased Nab3 assembly. Further, the C-terminal oligomerization domain of the Nab3 PrLD is important for condensate formation. Based on this, Nab3 granule formation has composition preference and primary sequence dependence, while SGs are compositionally dependent. Together, the mechanism of IDR assembly is not uniform among yeast condensates, with different sequence features being important based on the system.
Keywords: intrinsically disordered regions; phase separation; stress granules; Nab3 granule; biomolecular condensates; prion-like domains